Unexpected Encephalitis in Active Miliary TB Undergoing Treatment in an Elderly Person: A Rare Case Report - Digdoyo, Ananda; Tabuni, Carolus Boromeus; Wikrama, Ketut Wiswa; Putra, Putu Nanda Pratama; Atmoko, Mahendra Bagus Dwi; Sudharmadji, Sudharmadji (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2026)
Miliary tuberculosis (TB) with central nervous system (CNS) involvement manifesting as unexpected encephalitis in the elderly is a rare and serious condition. This study aims to describe and analyze the clinical manifestations of unexpected encephalitis in elderly patients with active miliary TB undergoing treatment. A descriptive case study with a qualitative approach was used. The population was elderly patients diagnosed with active miliary TB complicated by CNS involvement, with a purposive sample of one 68-year-old female patient who presented with atypical neurological symptoms after approximately five weeks of multidrug therapy (MDT). Data were obtained from medical records, neurological physical examinations, laboratory results, and head CT scans. A narrative descriptive analysis integrated clinical and radiological findings to interpret the relationship between encephalitis manifestations and TB therapy progression. The results showed atypical encephalitis symptoms with CT evidence of hypodense lesions and central calcifications, highlighting the diagnostic challenge. Appropriate MDT therapy with adjuvant corticosteroids resulted in a good clinical response. The conclusions emphasize the importance of early detection and use of neuroimaging in elderly patients with miliary TB to reduce neurological complications. Further research with larger samples is recommended to strengthen the findings.